Pojok Literasi Sebagai Upaya Meningkatkan Minat Baca Di Pulau Panjang, Lepar Pongok, Kabupaten Bangka Selatan - Prananda, Mustobi; Virlian; Ramadhan A. Iqbal; Lindiatika; Anjani, Tiara P.; Kurniawan, Ardiansyah (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Students Association of Himakuatik was implemented The Bina Desa program in Panjang Island, Penutuk Village, Lepar Pongok District, South Bangka Regency. Panjang Island is one of the isolated islands in the Bangka Belitung Islands which has a low literacy culture, especially among children. One of the causes of the low level of literacy skills of elementary school students in Panjang Island is due to the small collection of fiction and non-fiction reading books at school and at home. The purpose of the work program to create a literacy corner in Pulau Panjang is to provide reading facilities and form reading habits for Pulau Panjang children. The implementation of activities goes through several stages, namely preparation, implementation and evaluation. The results of the service obtained are the availability of literacy facilities in the form of a literacy corner and forming reading habits for children in Long Island Hamlet.